1995
DOI: 10.1128/jb.177.19.5653-5660.1995
|View full text |Cite
|
Sign up to set email alerts
|

Proteus mirabilis urease: operon fusion and linker insertion analysis of ure gene organization, regulation, and function

Abstract: Urease is an inducible virulence factor of uropathogenic Proteus mirabilis. Although eight contiguous genes necessary for urease activity have been cloned and sequenced, the transcriptional organization and regulation of specific genes within the Proteus gene cluster has not been investigated in detail. The first gene, ureR, is located 400 bp upstream and is oriented in the direction opposite the other seven genes, ureDABCEFG. The structural subunits of urease are encoded by ureABC. Previously, UreR was shown … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 54 publications
1
38
0
Order By: Relevance
“…Our study also showed that H. hepaticus ureE and ureG mutants are totally devoid of urease activity. These results were expected, because UreE and UreG have been shown to be required for urease activity in several micro-organisms, including H. pylori (Mehta et al, 2003a;Voland et al, 2003), Proteus mirabilis (Island & Mobley, 1995) and K. aerogenes (Mulrooney & Hausinger, 1990). As shown previously for H. pylori , nickel supplementation of the growth medium did not restore urease activity in either H. hepaticus mutant.…”
Section: Although Protein Sequences Of H Hepaticus and H Pylorisupporting
confidence: 55%
“…Our study also showed that H. hepaticus ureE and ureG mutants are totally devoid of urease activity. These results were expected, because UreE and UreG have been shown to be required for urease activity in several micro-organisms, including H. pylori (Mehta et al, 2003a;Voland et al, 2003), Proteus mirabilis (Island & Mobley, 1995) and K. aerogenes (Mulrooney & Hausinger, 1990). As shown previously for H. pylori , nickel supplementation of the growth medium did not restore urease activity in either H. hepaticus mutant.…”
Section: Although Protein Sequences Of H Hepaticus and H Pylorisupporting
confidence: 55%
“…Several studies referred to using of 16SrRNA for identification of P. mirabilis isolated from ocular infections [14], cerebrospinal fluid [15,16] who used specific primers for 16SrRNA gene to identify P. mirabilis and Proteus vulgaris that isolated from UTIs. 16SrRNA was described as a high discriminatory power for identification of bacteria and to differentiate between closely related genera because it exists in almost all bacteria, often existing as a gene cluster or operon, and also the function of this gene has not changed over time [17].…”
Section: Resultsmentioning
confidence: 99%
“…The P. mirabilis urease gene cluster, ureDABCEFG, is induced in the presence of urea and UreR, the transcriptional regulator of the gene cluster (D'Orazio & Collins, 1993D'Orazio et al, 1996;Island & Mobley, 1995;Nicholson et al, 1993). P. mirabilis UreR, a dimer of 33?4 kDa polypeptides is an AraC-like transcriptional regulator that activates transcription from p ureD and p ureR in a urea-inducible manner (D'Orazio et al, 1996;Island & Mobley, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…P. mirabilis UreR, a dimer of 33?4 kDa polypeptides is an AraC-like transcriptional regulator that activates transcription from p ureD and p ureR in a urea-inducible manner (D'Orazio et al, 1996;Island & Mobley, 1995). Thomas & Collins (1999) have shown, using electrophoretic mobility shift assay, that there are two binding sites for UreR in the ureR-ureD intergenic region, resulting in a major band shift at low concentrations of UreR (occupation of a single binding site) and an additional minor band shift at higher concentrations of UreR (occupation of two sites).…”
Section: Introductionmentioning
confidence: 99%